Communicative and Senior Content of Legal Documents - Selendili, L.S. (Âzyk i tekst, 2022)
The article considers the communicative and semantic content of a legal document. The purpose of the study: to determine whether the expression from clause X of the specified contract means "Termination of the contract is possible if the Lessee significantly violates the terms of this Agreement and by a court decision" termination of the contract if two conditions of "material violation" and "court decision" or one of the above conditions are met. To achieve this goal, a number of practical tasks have been solved related to the description of the lexico-grammatical compatibility of the word "perhaps" and the compositional union "and", taking into account the lexical and semantic, syntactic and functional features of the constructs of the sentence under consideration. The study was carried out by methods of description, observation, continuous sampling and is based on the method of contextual explication of conceptual-semantic and logical connections, which includes the analysis of the communicative-semantic (logical-conceptual) content of the utterance by correlating the studied. В статье рассматривается коммуникативно-смысловое содержание правового документа. Цель исследования: определить, означает ли выражение из п. Х указанного договора «Расторжение договора возможно при существенном нарушении Арендатором условий настоящего Договора и по решению суда» расторжение договора при выполнении двух условий «существенного нарушения» и «решения суда» или одного из вышеперечисленных условий. Для достижения поставленной цели решен ряд практических задач, связанных с описанием лексико-грамматической сочетаемости слова «возможно» и сочинительного союза «и» с учетом лексико-семантических, синтаксических и функциональных особенностей конструктов рассматриваемого предложения. Исследование выполнено методами описания, наблюдения, сплошной выборки и базируется на методе контекстной экспликации понятийно-семантических и логических связей, который включает в себя анализ коммуникативно-смыслового (логико-понятийного) содержания высказывания путем соотнесения исследуемого текста с понятийно-языковой ситуацией. Коммуникативно-смысловое содержание рассматриваемого правового документа является совокупностью лексико-семантических, синтаксических и функциональных особенностей конструктов рассматриваемого предложения.